IDV model for suspended sand transport under waves in ripple regime - Chung, Dang Huu (Vietnam Journal of Mechanics, 2000)
In this paper the results of theoretical studies on suspended sand transport under irregular waves in the ripple regime are presented. The results from the lDV model, which simulates the instantaneous velocity and sand concentration from close to the bed up to higher in the water column are obtained. The model is based on the classical diffusion approach taking both the turbulence-related and the effective wave related diffusion into account. It shows that the time-averaged sand concentrations can be simulated reasonably well in the ripple regime using calibrated equations. Especially, the proposed formula for the diffusion coefficient by wave, considerably improved the behavior of vertical distribution of upended sediment concentration. Finally, the wave related suspended sediment transport in depth-integration is computed and compared with the measured data. The accuracy of the suspended transport was found to be strongly dependent on using measured data or predictive formula for concentration at the bed boundary.